The Role of Popa in the Socio-Cultural Dynamics of the Dayak Siang Tribe - Delfiani Putri Rejeki (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2025)
Alcohol in the traditional form, such as popa, is not just an intoxicating drink. It is an integral part of the socio-cultural life of indigenous communities in Indonesia. Behind seemingly simple activities such as drinking popa lie cultural and social values that have been passed down from generation to generation. Through a qualitative approach and anthropological perspective, this study aims to provide a more open and comprehensive description and understanding of the role of popa in community life, how it is interpreted in a ritual context, and how this practice reflects the cultural dynamics, identity, and social structure of the local Dayak Siang community. The data in this study was obtained through participant observation, in-depth interviews, and literature review. The results of this study show that, specifically, popa is categorized into four symbols that cover the overall function and meaning of popa in the life of the Dayak Siang tribe. First, popa as a spiritual symbol, namely a connection between humans and ancestral spirits; second, popa as a social symbol, which strengthens community solidarity; third, popa as a cultural symbol, which preserves local identity and knowledge; and fourth, popa as a symbol of transition, which marks spiritual and social changes in the life cycle of the Dayak Siang community. On the other hand, the cultural transformation of popa drinking among the Dayak Siang tribe reflects the dynamics of cultural adaptation to social, economic, and ideological influences that have developed over time.